2016
DOI: 10.1177/0093854816683423
|View full text |Cite
|
Sign up to set email alerts
|

The Linguistic Output of Psychopathic Offenders During a PCL-R Interview

Abstract: We used text analysis software to examine the linguistic features of the speech of 21 psychopathic and 45 other offenders during the interview part of a Psychopathy Checklist–Revised (PCL-R) assessment. Regression analysis was run on the linguistic categories to determine which were the best predictors of psychopathy scores. Relative to the other offenders, psychopaths used more disfluencies (“you know”) and personal pronouns, made fewer references to other people (e.g., personal names, family), and were also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 53 publications
2
28
0
Order By: Relevance
“…Notably, their emotional language is overflowing with lexical inconsistencies. Some studies showed that while psychopaths speak about emotional events, they are less emotionally expressive, in particular, they produce anxiety related words less frequently and use less emotionally intense language (Brinke et al, 2017;Hancock et al, 2011;Hildebrand et al, 2004;Le et al, 2017). In contrary to these findings, psychopaths have been found to be more expressive in talking about anxiety, love, and hate (Gawda, 2010(Gawda, , 2013.…”
Section: Lexical Aspectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, their emotional language is overflowing with lexical inconsistencies. Some studies showed that while psychopaths speak about emotional events, they are less emotionally expressive, in particular, they produce anxiety related words less frequently and use less emotionally intense language (Brinke et al, 2017;Hancock et al, 2011;Hildebrand et al, 2004;Le et al, 2017). In contrary to these findings, psychopaths have been found to be more expressive in talking about anxiety, love, and hate (Gawda, 2010(Gawda, , 2013.…”
Section: Lexical Aspectsmentioning
confidence: 99%
“…In the context of syntax analysis focusing on psychopathic offenders' speech, it has been found that they use past tenses more frequently (Hancock et al, 2011), as well as repetitions, pauses, and negations in affective speech (Gawda, 2010). Some researchers point out to the lack of coherence in the psychopaths' speech, also in terms of logical reasoning as well as poor flow, stuttering, or rapid shifts in topic (Adshead, 2014;Brinkley et al, 1999;Hancock et al, 2011;Holmqvist, 2008;Le et al, 2017;Selenius & Strand, 2015;Williamson et al, 1991). It has been also observed that psychopathic offenders come to conclusions based on insufficient information (Gawda, 2013).…”
Section: Syntaxmentioning
confidence: 99%
See 2 more Smart Citations
“…Le et al [21] used a primary assessment tool, namely, PCL-R to investigate the discussion/language of offenders during the interview. Additionally, LIWC text analysis software program and Wmatrix method are used.…”
Section: Review Of Literaturementioning
confidence: 99%